Лiнiйнi нетеровi крайовi задачi для динамiчних систем на часовiй шкалi - Бойчук, О.А.; Страх, О.П. (Нелінійні коливання, 2014)
Встановлено необхiднi та достатнi умови розв’язностi нетерових крайових задач для систем динамiчних рiвнянь на часовiй шкалi. Дослiджено структуру множини розв’язкiв таких задач. Розглянуто приклад крайової задачi у випадку, коли часова шкала є канторовою множиною. We find necessary and sufficient conditions for solvability of a Fredholm boundary-value problem for a system of dynamical equations on a time scale. The structure of solutions of this boundary-value problem is researched. An example of a Fredholm boundary-value problem has been considered in the case where the time scale is the Contor set.